Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.ydbio.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of porcine embryos in vivo and in vitro; evidence for embryo ‘cross talk’ in vitro

Abstract: The in vitro development of zygotes of domestic species to the blastocyst stage is facilitated by culture in groups, suggesting a role for autocrine/paracrine factors. A novel method was used to investigate the potential role of such factors using in-vitro-produced and in-vivo-derived porcine embryos. The development of individual zygotes to the blastocyst stage was optimal when they were cultured 81-160 mum apart. As the distance between the embryos was increased, blastocyst rates declined significantly, reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 32 publications
3
68
1
1
Order By: Relevance
“…Single embryo culture results obtained here are very low, but this level is also observed in other works culturing embryos individually (sIVC), and even regrouped for the remaining steps (gIVM, gIVF) (Carolan et al, 1996;Ward et al, 2000;Goovaerts et al, 2009). It is suggested in several animal species (mice, bovine, porcine) that suppression of early development of embryos cultured individually might be caused by a deficiency of cooperative interaction among embryos (Paria and Dey, 1990;Keefer et al, 1994;Stokes et al, 2005). It seems that several growth factors could act as possible embryotrophic factors reciprocally stimulating embryo development, in a paracrine/autocrine fashion, when embryos are cultured in vitro in groups (Paria and Dey, 1990;Palma and Brem, 1995;Thibodeaux et al, 1995;Lim and Hansel, 1996;Stokes et al, 2005;Contramaestre et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Single embryo culture results obtained here are very low, but this level is also observed in other works culturing embryos individually (sIVC), and even regrouped for the remaining steps (gIVM, gIVF) (Carolan et al, 1996;Ward et al, 2000;Goovaerts et al, 2009). It is suggested in several animal species (mice, bovine, porcine) that suppression of early development of embryos cultured individually might be caused by a deficiency of cooperative interaction among embryos (Paria and Dey, 1990;Keefer et al, 1994;Stokes et al, 2005). It seems that several growth factors could act as possible embryotrophic factors reciprocally stimulating embryo development, in a paracrine/autocrine fashion, when embryos are cultured in vitro in groups (Paria and Dey, 1990;Palma and Brem, 1995;Thibodeaux et al, 1995;Lim and Hansel, 1996;Stokes et al, 2005;Contramaestre et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…It is suggested in several animal species (mice, bovine, porcine) that suppression of early development of embryos cultured individually might be caused by a deficiency of cooperative interaction among embryos (Paria and Dey, 1990;Keefer et al, 1994;Stokes et al, 2005). It seems that several growth factors could act as possible embryotrophic factors reciprocally stimulating embryo development, in a paracrine/autocrine fashion, when embryos are cultured in vitro in groups (Paria and Dey, 1990;Palma and Brem, 1995;Thibodeaux et al, 1995;Lim and Hansel, 1996;Stokes et al, 2005;Contramaestre et al, 2008). In addition, Nagao et al (2008) concluded that the cooperative interaction among bovine early embryos during in vitro culture may be also mediated by the reduction of toxic factors, so at low embryo density, reduced oxygen tension or the exclusion of inorganic phosphate from the medium enhances blastocyst development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the previous study of Stokes et al (2005), who could not demonstrate a significant effect on blastocyst development of a porcine embryo's position in a 4!4 grid. More importantly, it appears to be the developmental stage of the neighbours, and more specifically their development after 45 hpi, which positively affects the outcome of a particular embryo.…”
Section: Discussionsupporting
confidence: 94%
“…To date, contradictory reports have been published on the benefit of group culture over individual culture of human embryos (Rijnders & Jansen 1999, Spyropoulou et al 1999, Ebner et al 2010, Rebollar-Lazaro & Matson 2010, Tao et al 2013, whereas many studies have described the benefits of group culture for bovine (Donnay et al 1997, O'Doherty et al 1997, Goovaerts et al 2009, Wydooghe et al 2014, mouse (Paria & Dey 1990, Canseco et al 1992, Lane & Gardner 1992, Salahuddin et al 1995, pig (Stokes et al 2005) and cat (Spindler & Wildt 2002) embryos. The main reason for this beneficial effect of group culture on animal embryo development has been ascribed to the secretion of autocrine factors by preimplantation embryos, which act upon the embryo itself or on neighbouring embryos (Paria & Dey 1990, O'Neill 2008.…”
Section: Introductionmentioning
confidence: 99%